The association between living environment and out-of-hospital cardiac arrest risk in adults: the perspective of daily-life contexts - Yitong Liao; Hui Chen; Shuli Zhou; Yuanwei Fu; Qiangrong Zhai; Qingbian Ma; Yan Xiong; Suhong Zhou (Archives of Public Health)
Abstract Background Studying the spatial pattern of out-of-hospital cardiac arrest (OHCA) and its environmental impactors is crucial for both providing timely medical assistance and implementing preventative measures. Existing researches have mainly focused on natural and sociodemographic environments, usually at a macro- or meso-scale, while giving less attention to understanding the association between environment and OHCA risk from the perspective of daily-life contexts. Methods In this study, we utilized 1843 eligible OHCA cases from core districts of Beijing in 2020 and employed modified Besag-York-Mollié (BYM2) Bayesian models to investigate the association between living environment (consisting of food environment, physical activity environment, healthcare environment and leisure environment) and adult OHCA risk, as well as its age disparities, at a 1 × 1 km2 cell resolution. Results The results show that: (1) Fewer living environment factors are associated with the OHCA risk in the young/middle-aged group compared to the elderly group. (2) Unhealthy food destination like barbecue restaurants in living area is associated with increased OHCA risk in both age groups. (3) Facility inducing sedentary activity like chess rooms and healthcare facilities are associated with increased OHCA risk, but only among the elderly groups. (4) The decreased OHCA risk in the young/middle-aged group is related to public gathering places for socialization and relaxation in living area like coffee shops, while for the elder groups, decreased OHCA risk is associated with more green spaces in the living area. Conclusions The findings suggest that living environment may impact adult OHCA risk through shaping daily habits or providing access to health resources, with the underlying mechanism varying across different age groups. Future planning should fully consider and leverage the impact of living environment in order to effectively reduce OHCA risk.